Constituintes químicos das folhas de Senna spectabilis (DC) Irwin & Barneby var. excelsa (Schrad.) Irwin & Barneby - Fábio de Oliveira Silva; Írvila Ricarte de Oliveira; Maria Goretti de Vasconcelos Silva; Raimundo Braz-Filho (Química Nova, 2010)
From leaves of Senna spectabilis var. excelsa were isolated caffeine, the triterpenes lupeol, α-amyrin, β-amyrin, cycloeucalenol, friedelin and ursolic, oleanolic and betulinic acids, besides the steroids sitosterol and stigmasterol and their respective glucosides. The structures of these compounds were established by spectroscopic analysis including two-dimensional NMR methods and comparison with published spectral data. This paper deals with the first report of these compounds in S. spectabilis var. excelsa.